The Stability of the Adjusted and Unadjusted Environmental Kuznets Curve - Leonardo Becchetti; Sabrina Auci (Fondazione Eni Enrico Mattei (FEEM), 2005)
In our paper, we test the stability of the unadjusted and adjusted Environmental Kuznets Curve (EKC). Our results provide evidence in favour of the significance of the adjusted EKC hypothesis in which the impact of per capita GDP on the intensity of CO2 emissions is evaluated conditionally to the effects of the energy-supply infrastructure and of additional socio-demographic variables. In this framework, the GDP-CO2 relationship appears robust to the inclusion of additional regressors and to changes in the estimation period and interval
Keywords: Q53; 330; Sustainable development; Kuznets curve; CO2 emissions; Nachhaltige Entwicklung; Umweltbelastung; Wirtschaftswachstum; Luftverunreinigung; Welt; Environmental Kuznets Curve